2010
DOI: 10.1002/hep.23831
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glycemic Control with Colesevelam Treatment in Patients with Type 2 Diabetes Is Not Directly Associated with Changes in Bile Acid Metabolism

Abstract: Bile acids (BAs) are essential for fat absorption and appear to modulate glucose and energy metabolism. Colesevelam, a BA sequestrant, improves glycemic control in type 2 diabetes mellitus (T2DM). We aimed to characterize the alterations in BA metabolism associated with T2DM and colesevelam treatment and to establish whether metabolic consequences of T2DM and colesevelam are related to changes in BA metabolism. Male subjects with T2DM (n 5 16) and controls (n 5 12) were matched for age and body mass index. BA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
150
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(170 citation statements)
references
References 36 publications
15
150
3
2
Order By: Relevance
“…This may suggest that individual bile acids respond differently to BAS but also that the percentage contribution of newly synthesised cholesterol to CA vs CDCA may not depend on the total bile acid production rate. As shown previously [12], colesevelam treatment significantly reduced FGF-19 concentrations in both the fasting and the postprandial states. We also found that fasting and postprandial FGF-19 concentrations were negatively correlated with CDCA and CA synthesis in type 2 diabetes before treatment.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This may suggest that individual bile acids respond differently to BAS but also that the percentage contribution of newly synthesised cholesterol to CA vs CDCA may not depend on the total bile acid production rate. As shown previously [12], colesevelam treatment significantly reduced FGF-19 concentrations in both the fasting and the postprandial states. We also found that fasting and postprandial FGF-19 concentrations were negatively correlated with CDCA and CA synthesis in type 2 diabetes before treatment.…”
Section: Discussionsupporting
confidence: 85%
“…We also found that fasting and postprandial FGF-19 concentrations were negatively correlated with CDCA and CA synthesis in type 2 diabetes before treatment. Studies in healthy participants have suggested that BA synthesis is regulated in part by FGF-19 [12,48], but a similar relationship in type 2 diabetes was not seen in a previous study [12]. FGF-19 has been shown to inhibit fatty acid synthesis in cultured hepatocytes [49] and bile acid sequestration in diabetic db/db mice resulted in an increase in DNL [3].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations